2003
DOI: 10.1152/ajpheart.01106.2001
|View full text |Cite
|
Sign up to set email alerts
|

Development of electrical activity in cardiac myocyte aggregates derived from mouse embryonic stem cells

Abstract: Embryonic stem cells differentiate into cardiac myocytes, repeating in vitro the structural and molecular changes associated with cardiac development. Currently, it is not clear whether the electrophysiological properties of the multicellular cardiac structure follow cardiac maturation as well. In long-term recordings of extracellular field potentials with microelectrode arrays consisting of 60 substrate-integrated electrodes, we examined the electrophysiological properties during the ongoing differentiation p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
89
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(100 citation statements)
references
References 45 publications
10
89
1
Order By: Relevance
“…Several lines of arguments could explain this effect. For example, it was recently shown that larger beating areas of embryoid bodies display a higher beating frequency (Banach et al, 2003). As Tbx5 overexpression results in an increase in cardiomyocyte formation this might directly result in an increased beating frequency.…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of arguments could explain this effect. For example, it was recently shown that larger beating areas of embryoid bodies display a higher beating frequency (Banach et al, 2003). As Tbx5 overexpression results in an increase in cardiomyocyte formation this might directly result in an increased beating frequency.…”
Section: Discussionmentioning
confidence: 99%
“…Stem cell-derived myocytes grown in vitro can recapitulate the development and differentiation of cardiomyocytes very closely [92][93][94]. The accessibility of these cells and the relative ease by which they can be genetically manipulated (compared to myocytes in early embryos) has led them to be used for many studies of cardiac development.…”
Section: Ip 3 Signaling In Cardiac Developmentmentioning
confidence: 99%
“…multichannelsystems.com) [22][23][24]. For this aim, beating areas were mechanically removed and plated on MEA plates.…”
Section: Microelectrode Mappingmentioning
confidence: 99%